2018
DOI: 10.5751/ace-01190-130112
|View full text |Cite
|
Sign up to set email alerts
|

Postfledging survival and local recruitment of a riparian songbird in habitat influenced by reservoir operations

Abstract: ABSTRACT. The impact of anthropogenic activities on breeding bird populations are typically assessed using nest success despite the importance of the postfledging period and juvenile survival for the population dynamics of many birds. Using a combination of radio telemetry data collected between 2012 and 2014, and long-term monitoring data collected between 2005 and 2016, we evaluated whether postfledging survival of Yellow Warblers (Setophaga petechia) is affected when their riparian nesting habitat becomes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…We observed low mortality rates for rusty blackbird fledglings in the first week after fledging (3%) compared to those reported for other songbirds, e.g., 21-81% for ovenbird [2], 11% for worm-eating warbler [8], and 90% for rose-breasted grosbeak (Pheucticus ludovicianus) fledglings [7]. All observed fledgling mortality took place in the first four days of a yellow warbler (Setophaga petechi) study [58]. Our high rusty blackbird fledgling survival contrasts with virtually every other songbird post-fledging study.…”
Section: Survival and Habitat Selectionmentioning
confidence: 57%
“…We observed low mortality rates for rusty blackbird fledglings in the first week after fledging (3%) compared to those reported for other songbirds, e.g., 21-81% for ovenbird [2], 11% for worm-eating warbler [8], and 90% for rose-breasted grosbeak (Pheucticus ludovicianus) fledglings [7]. All observed fledgling mortality took place in the first four days of a yellow warbler (Setophaga petechi) study [58]. Our high rusty blackbird fledgling survival contrasts with virtually every other songbird post-fledging study.…”
Section: Survival and Habitat Selectionmentioning
confidence: 57%
“…Rising water levels do, however, coincide with the three-week post-fledging period when juveniles are dependent on their parents. Studies show this is a period of high mortality for songbirds [ 32 ], and we have shown that the survival of radio-tagged fledglings and the recruitment of colour-banded fledglings from inundated territories are lower than the survival and recruitment of fledglings from territories not inundated by water [ 17 ]. Our individual-based model estimates that under current reservoir operations rising water levels that extend into yellow warbler habitat (the riparian shrub zone at > 435m a.s.l.)…”
Section: Discussionmentioning
confidence: 99%
“…Females can nest multiple times during a breeding season (maximum = 3) and may renest after both failed and successful nesting attempts. Fledglings are independent of their parents after approximately 21 days [ 17 ].…”
Section: Study Site and Speciesmentioning
confidence: 99%
See 2 more Smart Citations